Parkinson's disease and the skin. Issue 4 (10th April 2015) - Gregory, Ralph; Miller, Sarah
Abstract : The concept that the skin is a mirror of Parkinson's disease dates to the start of the last century. Despite dermatological disorders being recognised as a common non-motor symptom of Parkinson's disease, they are often overlooked. This article reviews the various skin disorders seen in Parkinson's disease and addresses the other dermatological questions that are frequently raised by those attending Parkinson's disease clinics.